Antenatal breast milk expression at term increases postnatal lactational performance - Uikey, P. A.; Agrawal, Palak; Khandale, Surekha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Breast milk contains balanced nutrients for the complete growth of body and brain of neonates and infants. Breast feeding is rich in anti-infective factors and improves immune system, thus reducing the child mortality rate. Objective of present work was to study the effect of antenatal breast milk expression at term in improving lactational performance as compared to control group. Methods: The prospective, comparative study was conducted for 2 years to observe effects of antenatal expression of breast milk on postnatal lactational performance in a tertiary care centre in Central India. 200 Subjects after 37 weeks of pregnancy divided in two groups of 100 each 1) study group 2) control group by systematic random sampling technique. Prior examination was done to exclude any inverted or cracked nipples and appropriate treatment instituted. The women with diseased breast and conditions, high risk pregnancy, congenitally anomalous fetus and drugs affecting lactation were excluded from study. Study group women were counselled to express milk 2-3 times every day preferably during bathing. All women were followed up in hospital and postnatal lactation performance was observed in both groups. Results: The study group did not find it difficult to initiate breast feeding after vaginal or caesarean delivery and in 78% of patients time interval from initiation of lactation to establishment of lactation was less than half hour as compared to control group (38%) P value <0.001. Statistical analysis showed significant difference in the results of those groups. Conclusions: Daily antenatal breast milk expression after 37 weeks of pregnancy significantly reduced the time for establishing full breast feeding and reduced breast feeding failures.